Kinerja Program Pengembangan Kapasitas SDM dan Lembaga Kesejahteraan Sosial Studi Kasus di BBPPKS Regional I Sumatera - Agus Widiatmo (Jurnal Transformasi Administrasi, 2022)
The optimality of the implementation of social welfare, which refers to Law Number 11 of 2009 concerning Social Welfare and Permensos Number 6 of 2020 concerning the Ministry of Social Affairs Strategic Plan 2020-2024, will be largely determined by the quality of human resources and social welfare institutions. This research is aimed at uncovering the performance of the HR capacity building program and social welfare institutions in supporting the optimization of social welfare implementation in the 2017-2021 period, with a case study at BBPPKS Regional I Sumatera. The results of the study show that in terms of budget allocation and proportionality, the proportion of budget allocations for the capacity building program for HR and social welfare institutions at BBPPKS Regional I Sumatera compared to the total budget for Social Research and Education is below 8%, which is in the range of 5.44% to 7.54% . On the other hand, the lack of budget allocations and proportions did not affect the output per activity. In terms of target and output, out of a total of 25 education and training programs, 24 (96.00%) of them produced output and 1 other training activity (4.00%) with 150% realization, due to changes in learning formats from offline to online due to the situation and conditions of the covid pandemic. Regarding the realization of outcomes, the Non Apparatus Social Welfare HR training shows a better proportionalization of material substance based on the main function and supports the implementation of Social Welfare compared to the Apparatus Social Welfare HR training. The increase in knowledge, skills, internalization of values ​​was also felt by most of the alumni of the Social Welfare and Non-Apparatus HR training, which also had a significant effect on improving the quality of performance, both in the eyes of direct superiors and colleagues. In terms of cooperation with the Provincial and Regency/City local governments through the 1st pattern as an ideal pattern, it has only been able to reach 6 (75.00%) of 8 Provinces and 4 (3.03%) of 132 Regencies/Cities in regional I region Sumatera.